A novel reputation system for mobile app stores using blockchain - Mendes, G. S.; Chen, D.; Silva, B. M. C.; Serrão, C.; Casal, J. (Computer, 2021)
With thousands of mobile applications submitted to online application stores, the mobile application market has experienced significant growth. This growth is accompanied by an increase in malware presence. A possible solution would be to leverage those reports across all mobile ecosystems, creating a shared reputation system.